Oral mucosa lesions and risk habits: A cross-sectional study in North Serbia student ‎population - Milos Cankovic (Journal of Oral Health and Oral Epidemiology, 2015)
BACKGROUND AND AIM: Epidemiological studies have established a wide variation in the prevalence of oral lesions in different population. Officially oral mucosa diseases can occur in 25-50% of cases, depending on the population to which the survey was conducted. We examined the relationship between oral mucosal lesions, tongue pH level, gingivitis, oral hygiene, and oral health behaviors in student’s population.